2005
DOI: 10.1191/1352458505ms1118oa
|View full text |Cite
|
Sign up to set email alerts
|

Treating learning impairments improves memory performance in multiple sclerosis: a randomized clinical trial

Abstract: This randomized clinical trial utilized established techniques to improve new learning and memory performance in multiple sclerosis (MS) participants with learning impairment. Participants were 29 individuals with clinically definite MS with documented learning deficits, randomly assigned to the experimental or control group. The experimental group underwent eight sessions of the Story Memory Technique (SMT), while the control group participated in eight sessions of memory exercises. Neuropsychological assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
96
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(101 citation statements)
references
References 38 publications
3
96
0
2
Order By: Relevance
“…However, results of these experimental studies need to be translated into clinical trials and tested. Chiaravalloti et al 20 …”
Section: Results Of the Consensus Conference: Conclusion Of The Partmentioning
confidence: 99%
“…However, results of these experimental studies need to be translated into clinical trials and tested. Chiaravalloti et al 20 …”
Section: Results Of the Consensus Conference: Conclusion Of The Partmentioning
confidence: 99%
“…Turning presently to cognitive rehabilitation in MS (see O'Brien, Chiaravalloti, Goverover, & DeLuca, 2008, for a review), anterograde memory has been targeted in a number of studies and several rehabilitation methods have been probed that aimed at improving learning abilities in MS patients (Allen, Goldstein, Heyman, & Rondinelli, 1998;Basso, Lowery, Ghormley, Combs, & Johnson, 2006;Chiaravalloti & DeLuca, 2002;Chiaravalloti, Demaree, Gaudino, & DeLuca, 2003;Chiaravalloti, DeLuca, Moore, & Ricker, 2005;Goveover, Hillary, Chiaravalloti, Arango-Lasprilla, & DeLuca, 2009;Hildebrant et al, 2007;Mendozzi et al, 1998;Solari et al, 2004). Among them, the use of mental visual imagery (MVI) techniques lead to positive outcomes in relapsingremitting MS patients with moderate to severe memory impairment (Chiaravalloti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the use of mental visual imagery (MVI) techniques lead to positive outcomes in relapsingremitting MS patients with moderate to severe memory impairment (Chiaravalloti et al, 2005). However, an overview of anterograde memory rehabilitation in MS shows no general agreement either about the comparison of pre-and post-cognitive rehabilitation results or about the transfer of benefits in everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…Memory rehabilitation has been provided for people with multiple sclerosis withpromisingresults. [4][5][6][7][8][9][10][11] Interventions have mainly involved individual training on computerized tasks, 5,[7][8][9][10][11] but some have delivered face to face group sessions. 6 Although the findings from individual studies mostly appear promising, reviews of memory rehabilitation in people with multiple sclerosis have indicated that the effectiveness of memory rehabilitation programmes is far from conclusive.…”
Section: Introductionmentioning
confidence: 99%